Direct Monitoring of Initiation Factor Dynamics through Formation of 30S and 70S Translation–Initiation Complexes on a Quartz Crystal Microbalance. Issue 21 (27th March 2013) - Takahashi, Shuntaro; Isobe, Hidemi; Ueda, Takuya; Okahata, Yoshio
Abstract Translation initiation is a dynamic and complicated process requiring the building a 70S initiation complex (70S‐IC) composed of a ribosome, mRNA, and an initiator tRNA. During the formation of the 70S‐IC, initiation factors (IFs: IF1, IF2, and IF3) interact with a ribosome to form a 30S initiation complex (30S‐IC) and a 70S‐IC. Although some spectroscopic analyses have been performed, the mechanism of binding and dissociation of IFs remains unclear. Here, we employed a 27 MHz quartz crystal microbalance (QCM) to evaluate the process of bacterial IC formation in translation initiation by following frequency changes (mass changes). IFs (IF1, IF2, and IF3), N‐terminally fused to biotin carboxyl carrier protein (bio‐BCCP), were immobilized on a Neutravidin‐covered QCM plate. By using bio‐BCCP‐IF2 immobilized to the QCM, three steps of the formation of ribosomal initiation complex could be sequentially observed as simple mass changes in real time: binding of a 30S complex to the immobilized IF2, a recruitment of 50S to the 30S‐IC, and formation of the 70S‐IC. The kinetic parameters implied that the release of IF2 from the 70S‐IC could be the rate‐limiting step in translation initiation. The IF3‐immobilized QCM revealed that the affinity of IF3 for the 30S complex decreased upon the addition of mRNA and fMet‐tRNAfMet but did not lead to complete dissociation from the 30S‐IC. These results suggest that IF3 binds and stays bound to ICs, and its interaction mode is altered during the formation of 30S‐IC and 70S‐IC and is finally induced to dissociate from ICs by 50S binding. This methodology demonstrated here is applicable to investigate the role of IFs in translation initiation driven by other pathways.